FASILITAS MADRASAH MAS AL-WASHLIYAH 22 TEMBUNG KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG SUMATERA UTARA - Amiruddin Siahaan; Nurika Khalila Daulay; Ahmad Risqi Syahputra Nasution; Mahanum Mahanum; Aini Maimanah (Universitas Indraprasta PGRI, 2022)
Purpose of this research is as for classify and reflect all elements the planning of MAS Al-Washliyah Tembung's facilities and infrastructure, such as procurement,use, inventory, elimination, inhibition, and support. This is a qualitative study that use a descriptive analytical technique. Interviews, observations, and documentation studies were used to gather information. Data validity testing, descriptive interpretation, increased involvement, auditing, and other steps are all part of the data analysis process. Facilities and infrastructure planning is done by conveying support as in government, infrastructure and facility procurement is done in agreement with facility planning, use, as well as the upkeep of assets and infrastructure done according to student needs, inventory is done annually according to data provisions, and goods deletion is done on a regular basis. Lack of services and amenities infrastructure are some of the most key aspects of every organization company consider consider challenges at facility management, however madrasa facilities are enough. According to the research. In this study, madrasas place a greater emphasis on the need of strategically situating student facilities so that users have a favorable experience